Al-Jala Hospital Experience on Total Knee Arthroplasty - Bayio , Salah; Hussein, Ramzi Ahmed (Al-Mukhtar Journal of Sciences, 2018)
The aim of this Prospective study was to analyze the results and our experience in the knee Arthroplasty for the management of primary osteoarthritis at aljala teaching hospital in Benghazi. From January 2007 to December 2008, our orthopedic department; male orthopedic A ( MOA ) and female orthopedic word ( FOW ) operated 60 knees of 55 patients. 43 of them were females (78%) and 12(22%) were males, and the mean age was 56 years.We recorded patient’s details; age, sex, Right or Left knee days of staying in hospitalization, Classification of OA [primary or secondary], time of operation, and associated diseases [hypertension, Diabetes mellitus, Ischemic heart disease]. A physical examination to assess knee motion, stability, strength, and overall leg alignment and X-rays (radiographs) to determine the extent of damage and deformity of the knee. Post operative complications and Revision. At final evaluation after a minimum period of 3 years; 5(9%) patients had bilateral total knee replacement, 32 right knee patients (58%), and 23left knee patients (42%). Loosening tibial component was found in two patients (3.6%), and one patient(1.8%) was complicated by postoperative infection. Patients with rheumatoid arthritis showed more improvement than those with osteoarthritis. The conclusions with regards to the differential treatment of women are almost two-thirds as likely to undergo a TKA as men. Elective TKA is an effective treatment option for end-stage osteoarthritis of the knee.